Association between DNA methylation profile and malignancy in follicular-patterned thyroid neoplasms. Issue 4 (April 2019) - Affinito, Ornella; Salerno, Paolo; D'Alessio, Alfonso; Cuomo, Mariella; Florio, Ermanno; Carlomagno, Francesca; Proietti, Agnese; Giannini, Riccardo; Basolo, Fulvio; Chiariotti, Lorenzo; Cocozza, Sergio; Santoro, Massimo
Abstract : Molecular differentiation between benign (follicular thyroid adenoma (FTA)) and malignant (follicular thyroid carcinoma (FTC)) thyroid neoplasms is challenging. Here, we explored the genome-wide DNA methylation profile of FTA (n.10) and FTC (n.11) compared to normal thyroid (NT) (n.7) tissues. FTC featured 3564 differentially methylated CpGs (DMCpG), most (84%) of them hypermethylated, with respect to normal controls. At the principal component analysis (PCA), the methylation profile of FTA occupied an intermediate position between FTC and normal tissue. A large fraction (n. 2385) of FTC-associated DMCpG was related (intragenic or within 1500 bp from the transcription start site) to annotated genes (n. 1786). FTC-hypermethylated genes were enriched for targets of the Polycomb transcriptional repressor complex and the specific histone H3 marks (H3K4me2/me3-H3K27me3) found in chromatin domains known as 'bivalent'. Transcriptome profiling by RNAseq showed that 7.9% of the DMCpGs-associated genes were differentially expressed in FTC compared to NT, suggesting that altered DNA methylation may contribute to their altered expression. Overall, this study suggests that perturbed DNA methylation, in particular hypermethylation, is a component of the molecular mechanisms leading to the formation of FTC and that DNA methylation profiling may help differentiating FTCs from their benign counterpart.